Biohemijski i hematološki nalazi i faktori rizika povezani sa oštećenjem bubrega kod pacijenata sa COVID-19 - Yaghmour, Yosra; Shraim, Ala'a; Abbas, Manal (Journal of Medical Biochemistry, 2022)
Background : COVID-19 is a new pandemic that has infected millions of people worldwide and caused a high rate of morbidity and mortality. COVID-19 may have a harmful effect on body organs especially, the kidneys.Aims: The main aim of our research is to study the association between the severity of COVID-19 disease and biochemical parameters related to kidney function and to investigate certain risk factors of COVID-19-associated kidney disease.Methods: A total of 174 individuals, 121 COVID-19 positive and 53 COVID-19 negative were enrolled in this study. The relation between COVID-19 infection, severity, kidney function test, hematological indicators were examined.Results: The most prominent symptoms among COVID-19 were fever (95%) and fatigue (92%). Regarding biochemical parameters, median creatinine, MPV, and CRP were found to be significantly higher in COVID-19 patients, whereas median eGFR, Na⁺, WBC, MCH, MCHC, and eosinophil percentage were significantly lower in this group. Severely infected patients were observed to have higher urea, creatinine, neutrophils, and NLR. However, median sodium, eGFR, hemoglobin, hematocrit, RBC, lymphocytes, and platelets count were significantly lower in the severe group. Urine examination of severe group showed a significantly lower specific gravity, while urine pH, protein, and glucose were significantly higher.Conclusion : Our analysis indicates that COVID-19 infection affects kidney function mainly creatinine level, urea, eGFR, Na⁺ and urine protein. Additionally, comorbidities such as older age (≥65), hypertension, taking medications, and CRP (≥33.55mg/L) are considered risk factors which are more likely to contribute to kidney impairment in COVID-19 positive patients.